Peran Psikologi Manajemen dalam Menciptakan Lingkungan Kerja Yang Kondusif di Sekolah - Siti Najmiyyatul Aliyyah; Nova Lutvita Ramadani; Lia Afifatur Rofiah; Lu’lu’ul Muhimah Nabilatul Maulidiyyah; Mu’alimin Mu’alimin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Management psychology in education is an interdisciplinary field that integrates the principles of psychology and management to improve the effectiveness of educational institution management. This study aims to understand how management psychology plays a role in creating a conducive work environment in schools. The research method used is a literature study by analyzing various relevant academic sources. The results of the study indicate that the application of management psychology contributes to improving the leadership of school principals, understanding the needs and personalities of teachers and employees, assisting in decision making, and overcoming conflict and stress in the work environment. The main factors that influence a healthy work environment include physical, psychological, and institutional policy aspects. By implementing strategies based on management psychology, educational institutions can create a work atmosphere that supports the productivity and well-being of all stakeholders.